Arterial hypertension perpetuates alveolar bone loss - Vanderlei, Janine Montenegro Toscano Moura de Medeiros; Messora, Michel Reis; Fernandes, Patrícia Garani; Novaes Jr., Arthur B.; Palioto, Daniela Bazan; Grisi, Marcio Fernando de Moraes; Souza, Sergio Luis Scombatti De; Gerlach, Raquel Fernanda; Silva, Cristina Antoniali [UNESP]; Taba Jr., Mario (My University, 2013)
Few studies have focused on the impact of hypertension on the progression of periodontitis (PD). The purpose of this study was to evaluate whether hypertension affects PD by enhancing bone loss even after the stimulus for PD induction is removed. Ligature-induced PD was created on the first mandibular molars of spontaneously hypertensive rats (SHR) and normotensive rats (Wistar Kyoto-WKY). The animals were assigned to non-ligated controls (C) and PD groups: WKY-C, WKY-PD, SHR-C, and SHR-PD. After 10 days, five animals of each group were killed and the ligatures of the other animals were removed. On the 21st day (11 days without PD induced), the remaining animals were killed. The jaws were defleshed and the amount of bone loss was measured. After 10 days, the PD groups showed more bone loss than its controls (P < .05); SHR-PD = 0.72 ± 0.05 mm, SHR-C = 0.39 ± 0.04 mm, WKY-PD = 0.75 ± 0.04 mm, and WKY-C = 0.56 ± 0.04 mm. The cumulative bone loss on day 21 (0.94 ± 0.13 mm) was significantly worse than on day 10 only in SHR-PD group (P < .05). The final bone loss differences between PD and C groups accounted for 102% (SHR) and 26% (WKY) increase in comparison with the initial control levels. Hypertension is associated with progressive alveolar bone loss even when the stimulus for PD induction is removed and it may be speculated that host condition perpetuates alveolar bone loss. © 2013 Informa Healthcare USA, Inc.
Keywords: Alveolar bone loss; Animal model; Hypertension; Periodontitis; SHR; alveolar bone loss; animal cell; animal experiment; animal model; animal tissue; bone metabolism; controlled study; disease association; hypertension; jaw; male; mandible; molar tooth; morphometrics; nonhuman; osteolysis; periodontitis; rat; Alveolar Bone Loss; Animals; Disease Models, Animal; Disease Progression; Ligation; Male; Rats; Rats, Inbred SHR; Rats, Inbred WKY